Synthesis and self-assembly of monodispersed metal-organic framework microcrystals - Lu, Guang (2014)
How to make super latt(ic)e: Monodispersed octahedral microcrystals of a zirconium-carboxylate metal-organic framework (MOF), UiO-66, were synthesized, under optimized experimental conditions, by using acetic acid as a modulator. Due to their uniform size and shape, the obtained MOF microcrystals can be assembled not only into large-area two-dimensional (2D) monolayers with oriented facets through a liquid-air interfacial assembly technique, but also into long-range three-dimensional (3D) superlattices by sedimentation.